MAIN CHARACTER IN THE NOVEL DI BIBIRNYA ADA DUSTA BY MIRA WIJAYA LIES AND THEIR IMPLICATION FOR INDONESIA LEARNING - Sri Mulyani (Universitas Indraprasta PGRI, 2020)
Abstract: This study aims to describe the main character in the novel Di Bibirnya Ada Dusta. The method used for research was descriptive qualitative method. To analyze the data, researchers used analytic and dramatic approaches, Semi (in Djojosuroto, 2009: 119). Analytic approach was an approach that describes the character or character by describing the character directly, while the dramatic approach was the approach used by the author in describing the character indirectly. The technique of collecting data in this research is first reading the novel carefully, then marking the parts related to the analytic and dramatic aspects of the main character, the focus of the research, namely the novel Di Bibirnya Ada Dusta by Mira Wijaya, while the became a research sub-focus related to the attitudes and actions of the main characters. After researching it can be concluded, the main character in this novel, namely Ray and Roy. Ray's attitude can be seen from an analytical aspect, which is serious and a liar, while the dramatic attitude depicts Ray's physical athletic, macho, handsome, handsome, and intelligent, while Roy has a physical similar to Ray's when viewed in dramatic terms, namely handsome, macho, intelligent, athletic, and imaginative, while the analytical aspects of Roy's attitude, namely boredom, imaginative, brave, and liar. The results of this study will be used to provide teaching in Indonesian language and literature. With the aim, so students can enhance appreciation, be able to appreciate, and be able to recognize the character of the character that the author has described. Keywords: Character, Novel, and Literature Learning.